Hemodynamic numerical simulation of aortic arch modular inner branched stent-graft in eight early patients from the first-in-human case series - Zhu, Yating; Li, Fen; Zhang, Hongpeng; Song, Hui; Ma, Xiaodan; Cao, Long; Zhang, Wenjun; Guo, Wei (Frontiers in Cardiovascular Medicine, 2022)
Background The modular inner branched stent-graft (MIBSG) (WeFlow-Arch™) is an emerging device for challenging aortic arch pathologies. Hemodynamic numerical simulation is conducive to predicting long-term outcomes as well as optimizing the stent-graft design. Objective This study aims to analyze the hemodynamic characteristics of the MIBSG devices based on numerical simulation analyses. Methods From June 2019 to June 2021, MIBSGs were utilized in eight cases. Numerical simulation analyses of branch perfusion and indicators including the time-averaged wall shear stress, oscillatory shear index, and relative residence time were performed. Results Lesions involved Zone 1 (n = 2), Zone 2 (n = 4), and Zone 3 (n = 2). Branched stent-grafts were deployed in the innominate artery and left common carotid artery (n = 5) or in the innominate artery and left subclavian artery (n = 3). The hemodynamic change in common was increased perfusion in the descending aorta and left common carotid artery. Half of the patients had increased cerebral perfusion of 8.7% at most, and the other half of the patients showed a reduction of 5.3% or less. Case 3 was considered to have acquired the greatest improvement in hemodynamic features. Conclusion The MIBSG showed improved hemodynamic features in most cases. The design of the MIBSG could be partly modified to acquire better hemodynamic performance.